(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Cannabis has become one of the most consumed illicit drugs throughout the world. Along with the time, Changes in law i. e. legalization/ decriminalization for its problematic utilization. Although, cannabis is also used for medicinal purposes to control pain, neurodegenerative disorders, etc. Cannabinoids can be identified from various biological such as blood, urine, saliva, etc for days/weeks after usage due to their retention depending on the frequency and length of exposure. In this review study, various methods for extraction and quantification such as solid phase extraction, liquid chromatography-mass spectrometry along with MEPS, LC-MS/MS, solid phase extraction, etc. of cannabinoids were studied from the body fluids. These methods not only helped in the detection of traces from biological evidence but also help in the determination of time since the occurrence.